Anti-Diarrheal Activities of Hydromethanolic Crude Extract and Solvent Fractions of Acacia seyal (Fabaceae) Roots in Mice - Mengesha AK; Birru EM; Adugna M (Dove Medical Press, 2022)
Assefa Kebad Mengesha, Eshetie Melese Birru, Meaza Adugna Department of Pharmacology, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Assefa Kebad Mengesha, Email asielove23@gmail.comBackground: Traditionally, the root of Acacia seyal is used for the treatment of diarrhea. However, its efficacy has not been scientifically evaluated. Thus, this study aimed to validate the antidiarrheal activities using hydromethanolic crude extract and solvent fractions of Acacia seyal roots in mice.Methods: In each model, mice were divided into five groups of six mice at random. Group I mice (negative controls) were given 1mL/100 g distilled water for hydromethanolic crude extract tests as well as n-hexane, ethyl acetate and aqueous fractions, while groups II, III, and IV were given 100 mg/kg, 200 mg/kg, and 400 mg/kg of hydromethanolic crude extract or solvent fractions. Group V mice (positive control) were given 3 mg/kg Loperamide for the castor oil-induced diarrhea and enteropooling test. All of the doses were taken orally. However, Atropine sulfate, 5 mg/kg, was given intraperitoneally for the gastrointestinal motility test. Statistical Package for the Social Sciences (SPSS) version 26 was used to examine the statistical significance of differences in the number and weight of wet and total feces, distance traveled by a charcoal meal, and intestinal fluid accumulation across groups.Results: When compared to the vehicle-treated group, the crude extract and n-hexane fraction notably delayed the onset of diarrhea, reduced the weight and volume of intestinal contents, and hindered the intestinal transit at all tested doses (P < 0.001). The ethyl acetate fraction also significantly (P < 0.001) decreased the weight of intestinal content at all doses examined. Only at 400 mg/kg did the aqueous fraction statistically (P < 0.01) prolonged the onset of diarrhea and impeded gastrointestinal motility.Conclusion: According to this study, the hydromethanolic crude extract and solvent fractions of Acacia seyal roots have promising antidiarrheal effects.Keywords: antidiarrheal, Acacia seyal, castor oil, enteropooling, gastrointestinal motility